HUBUNGAN SIMULTAN ANTARA MANAJEMEN LABA DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Nanintha Gemala Hadiatullah; Dwi Ratmono (Diponegoro Journal of Accounting, 2015)
This study aims to examine the simultaneous relationship between earnings management and corporate social responsibility disclosure. This study uses several control variables including the size of the company, the size of the profitability, market to book ratio, leverage, the auditor, auditor changes and the size of the Board of Commissioners. The population in this research is the manufacturing companies listed on the Indonesia stock exchange in 2010-2013. A total of observations used in the study was 232 companies. Analytical techniques used are the Ordinary Least Square (OLS) and Two-Stage Least Square (2SLS). The results of the analysis show that the corporate social responsibility disclosure has no effect on the earnings management. Vice versa, the earnings management has no influence on corporate social responsibility disclosure.